Bioethanol Production from Lignocellulosic Wastes: Potentials and Challenges - Erdoğan, Esra Meşe; Karagöz, Pinar; Özkan, Melek (Springer Science and Business Media Deutschland GmbH, 2023)
The need for new energy sources is becoming more evident due to the increase in global population, development of industrialization, and limitations in the recovery, supply, and use of fossil fuels. Second-generation bioethanol produced from lignocellulosic agricultural wastes by fermentation is regarded as a reliable alternative energy source in terms of the food-water-energy security nexus as it will enable the use of lignocellulosic wastes remaining in agricultural lands and have a low contribution to greenhouse gas emission. Although lignocellulosic bioethanol production technology has great potential, there are some challenges preventing the widespread use of this energy including difficulty in removing lignin, costly enzymes for efficient saccharification, insufficient fermentation of sugars other than glucose found in the structure of lignocellulose, and limited ethanol production due to product inhibition. Recent studies show that new methods and technologies can solve these obstacles. In this chapter, the potential of lignocellulosic bioethanol is evaluated by analyzing new processes or inventions in the 2G bioethanol industry and the complex dynamics of the sector. © 2023 Elsevier B.V., All rights reserved.
Keywords: Bioethanol; Cellulases; Fermentation; Lignocellulosic wastes; Saccharification